2022
DOI: 10.20884/1.jm.2022.17.1.5594
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids from the Stem bark of Aglaia elaeagnoidea and their cytotoxic activity against HeLa and DU145 Cancer Cell lines

Abstract: Aglaia is the largest genus of the Meliaceae family which contains terpenoid compounds. This type of compounds showed a diverse structures and biological activities that can be found in natural resources. Aglaia elaeagnoidea is a species from Aglaia genus that only has a few previous research. This study was aimed to isolate and determine the chemical structure of terpenoid compounds from the ethyl acetate extract of A. elaeagnoidea stem bark. Ethyl acetate extracts were separated and purified by various chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Furthermore, the FTIR spectrum showed the appearance of hydroxyl (3457 cm −1 ), gem -dimethyl (1380 cm −1 ), and ether groups (1055 cm −1 ). The 13 C NMR ( Table 1 ), along with the DEPT 135° and 1 H-NMR spectra ( Table 2 ), demonstrated that the NMR data of 1 had high similarity with the 20 S ,24 S -epoxy-3α,25-dihydroxy-dammarane isolated from A. elaeagnoidea [ 35 ]. A 2D NMR spectrum of this compound ( Figure 2 ) was also obtained to determine the exact structure of compound 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the FTIR spectrum showed the appearance of hydroxyl (3457 cm −1 ), gem -dimethyl (1380 cm −1 ), and ether groups (1055 cm −1 ). The 13 C NMR ( Table 1 ), along with the DEPT 135° and 1 H-NMR spectra ( Table 2 ), demonstrated that the NMR data of 1 had high similarity with the 20 S ,24 S -epoxy-3α,25-dihydroxy-dammarane isolated from A. elaeagnoidea [ 35 ]. A 2D NMR spectrum of this compound ( Figure 2 ) was also obtained to determine the exact structure of compound 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectrum presented the appearance of a gem -dimethyl (1387 cm −1 ) and a carbonyl group (1715 cm −1 ). The 13 C NMR ( Table 1 ), DEPT 135°, and 1 H-NMR spectra ( Table 3 ) demonstrated that the NMR data of compound 6 had high similarity with cabraleahydroxy lactone isolated from A. elaeagnoidea [ 35 ]. The sole distinction was the addition of an acetyl group at compound 6 , which was identified based on the addition of two carbon atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] 2.Cytotoxic Activity: Bark from the stem of A. elaeagnoidea was acquired from the Bogor Botanical Garden located in Bogor, West Java, Indonesia. [4] The plant's identification was supplied by the Bogor, Indonesia, Botanic Gardens of the Centre for Plant Conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Novel dammarane-type triterpenoids isolated from A. eximia and A. smithii were cytotoxic against P388 murin leukemia cells [ 6 , 23 ]. Oktaviani et al [ 24 ] isolated three dammarane-type triterpenoids and showed cytotoxicity against cervical (HeLa) and human prostate cancer cells (DU145). Therefore, they can be used as an anticancer agent in the future.…”
Section: Introductionmentioning
confidence: 99%